(untitled) (Journal of the College of Basic Education, 2022)
The research included five chapters, as the importance of the research lies in developing a training curriculum for aerobics to know its effect on some components of women’s health fitness. As the approach used in fitness centers focuses on losing weight as a primary goal without referring to the interest in measuring the general health level of women and their physical and physiological capabilities. The research objectives were to develop a training curriculum for aerobic exercises. And to identify the effect of the curriculum used on some components of healthy fitness.